Pengaruh Konsentrasi Kepemilikan Terhadap Risiko Environmental, Social, Governance (ESG) - Simamora, Alex Johanes (Jurnal Bingkai Ekonomi (JBE), 2025)
The success of environmental, social, governance (ESG) implementation can be seen from the effectiveness of ESG in reducing business risk. An effective governance structure ensures control and supervision of ESG implementation. Most of the ownership structures of companies in Indonesia are dominated by concentrated ownership. This study aims to examine the effect of ownership concentration on ESG risk. The research sample includes 210 companies listed on the IDXESG index in the 2020–2023 period. Data analysis was carried out using the regression method. Based on the results of the analysis, ownership concentration has been shown to reduce ESG risk. Controlling shareholders can encourage managers to implement ESG effectively in order to reduce business risk. Supervision by shareholders tends to be directed towards the interests of business sustainability by limiting managers' opportunistic behavior. This study contributes to the literature, especially agency theory, by expanding its context to ESG risk. This study also presents new evidence regarding the relationship between ownership concentration and ESG risk. The implications of this study are aimed at management to improve the monitoring function through ownership concentration, to regulators to formulate regulations related to ESG risk as part of ESG evaluation, and to investors to consider investing in companies with low ESG risk levels.